Policy Strategies to Improve Performance and Productivity of Marine Logistics - Muhammad Firdaus Bin Yusup (Collaborate Engineering Daily Book Series, 2024)
This article discusses policy strategies that can be implemented to improve the performance and productivity of the maritime logistics sector. Maritime logistics is an important component in the global supply chain, so it is important to continuously improve its performance. Several policy strategies that can be considered include investment in infrastructure and technology, simplification of procedures and regulations, development of human resource competencies, as well as international cooperation and coordination between stakeholders. The aim of implementing these strategies is to increase the efficiency, speed, reliability, and productivity of maritime logistics services as a whole, thereby contributing to increased competitiveness and economic growth.